"It's Only Other People Who Make Me Feel Black": Acculturation, Identity, and Agency in a Multicultural Community. Issue 1 (18th February 2013) - Howarth, Caroline; Wagner, Wolfgang; Magnusson, Nicola; Sammut, Gordon
<x xml:space="preserve">Abstract</x> This article explores identity work and acculturation work in the lives of British mixed‐heritage children and adults. Children, teenagers, and parents with mixed heritage participated in a community arts project that invited them to deliberate, construct, and reconstruct their cultural identities and cultural relations. We found that acculturation, cultural and raced identities, are constructed through a series of oppositional themes: cultural maintenance versus cultural contact; identity as inclusion versus identity as exclusion; institutionalized ideologies versus agency. The findings point towards an understanding of acculturation as a dynamic, situated, and multifaceted process: acculturation in movement. To investigate this, we argue that acculturation research needs to develop a more dynamic and situated approach to the study of identity, representation, and culture. The article concludes with a discussion on the need for political psychologists to develop methods attuned to the tensions and politics of acculturation that are capable of highlighting the possibilities for resistance and social change.